Academician Vsevolod Аrutiunovych Lazarian (1909‒1978) ‒ scientist, pedagogue, institutor of science and education (Celebrating 110 years since the birth) - N. V. Ustiak (History of science and technology, 2018)
This article depicts the main stages of life, research and scientific, scientifically-organizational, pedagogic and public activity of the outstanding national scholar in the area of mechanics and railway transport, National Ukrainian prize-winner, academician of the Academy of Sciences of Ukraine - Vsevolod Arutyunovich Lazarian. This article indicates that he is the author of more than 300 published works in the field of mechanics- monographs, articles, manuals, and more than 20 invention certificates and patents. The theoretical studies of transitional modes of trains of V. A. Lazarian has always been supported by experimental research in trains and staging in test laboratories for experiments on electronic models of rolling stock.The work of V. A. Lazarian is also essential for practice, in which transition modes of motion of complex mechanical systems are investigated, with elements in the form of capacities, which are partially filled with liquid. The results of studies of transitional modes of trains are described and summarized in the monograph V. A. Lazarian"Investigation of Unspecified Traffic Train Mode", as well as in a number of articles. The great importance to theory and practice had the creation of V. A. Lazarian the theory of stability of motion of rail vehicles. Relying on the results of fundamental research of O. M. Liapunov in the direction of stability of movement, V. A. Lazarian has developed and used a number of methods for studying the stability of the movement of rail carriages. These methods allowed not only to develop engineering methods for assessing the stages of stability of the existing types of rolling stock, but also to put and solve the problem of finding such parameters of vehicles, in which their motion is stable in a given range of speeds. And these studies were supported by well-established experiments. 1972-1973 years under the guidance of V.A. Lazarian tests of a high-speed wagon-lab were carried out, during which for the first time in the former USSR the speed of rail transport was reached 250 km/h. Parameters of the spring suspension of the tested wagon-lab were determined earlier by V.А. Lazarian and his students on the basis of the developed theory of the stability of movement of rail carriage. They were such that the carriage movement, as it turned out from the theory, proved to be stable throughout the range of speeds. There was also a series of special experiments in which a high-speed wagon-lab with some structural changes was used. The results of these experiments convincingly confirmed the main provisions of the theory.